(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
Free time is an aspect in life of educative subjects that allows them to develop in academic, personal and professional areas. The proper use of this time is a crucial factor that, depending on how it is used, will have a positive or negative impact. Due to unstructured use of free time, people spend a lot of time behind electronic devices that encourage unhealthy leisure activities. This research aims to analyze the importance of the proper use of free time in the educative subject with the purpose of verifying what benefits its proper use can have. Through a bibliographical review, it is determined that a productive use of free time is important to develop healthy habits and adequate social, emotional and cognitive skills in order to integrate into a changing world.